All-cause mortality and the risk of stroke with selective aspiration thrombectomy in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention: A nationwide retrospective cohort study. Issue 22 (29th May 2020) - Tung, Ying-Chang; See, Lai-Chu; Chang, Shu-Hao; Tu, Hui-Tzu; Chan, Yi-Hsin; Chang, Chi-Jen
Abstract : Abstract: Few data exist on the clinical outcomes of selective aspiration thrombectomy during primary percutaneous coronary intervention (PPCI). This was a nationwide retrospective cohort study. Patients who were diagnosed with ST-elevation myocardial infarction (STEMI) and received primary percutaneous coronary intervention (PCI) from July 2009 to December 2011 were identified from the National Health Insurance Research Database of Taiwan. Propensity score weighting was used to balance the covariates between the 2 study groups. The primary endpoints were all-cause mortality and stroke during hospitalization and at 30 days and 1 year of follow-up. Subgroup analyses were performed based on the hospital and physician volume of primary PCI. A total of 9100 ST-elevation myocardial infarction patients (29.4% of patients receiving aspiration thrombectomy and conventional PPCI vs 70.6% receiving PPCI alone) were identified. The incidence rates of all-cause mortality were comparable between the 2 groups during hospitalization (21.0 vs 27.37/100 person-months; P  = .29) and 1-year follow-up (0.81 vs 1.26/100 person-months; P  = .85). There were no significant differences in the stroke rates between the 2 groups during hospitalization (1.1 vs 2.34/100 person-months; P  = .3) and 1-year follow-up (0.09 vs 0.15/100 person-months; P  = .85). For the patients who survived to discharge, the post-discharge 1-year mortality was lower in the aspiration thrombectomy group of patients in whom the procedures were performed by physicians with a high volume of PPCI (hazard ratio: 0.47; 95% confidence interval: 0.24–0.94; P  = .03). In this nationwide cohort study, selective aspiration thrombectomy at the operation's discretion had a comparable mortality rate compared with PCI alone and did not increase the risk of stroke. In the patients treated by physicians with a high volume of PPCI, aspiration thrombectomy appeared to have a beneficial effect on post-discharge survival at 1 year. Abstract : Supplemental Digital Content is available in the text